DISTRIBUSI SUBSTRAT DI DALAM FIXED BED REACTOR (FBR) - Padmono, Djoko (Jurnal Teknologi Lingkungan, 2007)
Fixed Bed Reactor was the biological wastewater treatment reactor thatwas one of the Cakung Slaughterhouse (RPH Cakung) wastewatertreatment. Biological wastewater treatment process in principle wasprocess use of the microorganism to degrade the wastewater pollutant,where the wastewater will be changed into gas and the particle bio-solidthat enabled to be sediment. The capability of the microorganismdegrading this pollutant was influenced by various factor, some amongthem were the distribution of the substrate (microorganism group) inthe reactor. The distribution of this substrate could be known bymeasuring the value of pH and organic content as Chemical OxygenDemand (COD) or Total Solid (TTS). Considering the importance of theparameter then must be keep so that both of them, did not exceedlimits that were allowed in the FBR operation. This paper was discussedby the condition for the distribution of the substrate in various hydraulicretention time (HRT). Analysis was held for the operation with the up-flow system. Results of the research could be known that the value ofthe pH and TS in various HRT relatively constant, that is between 6.93– 7.15 (for the pH) and 0.32% - 0.56% (for TS). This value is still inlimits that were allowed. This showed that the FBR reactor had thegood performance was inspected from the condition for the distributionof the substrate inside.